Differences in Cardiometabolic Biomarkers Between Overweight/Obese vs. Healthy Weight Elementary-School Aged Latino Children. (29th May 2020) - McKay, Allison; Gallo, Sina; Posada, Daisy; Fields, Jennifer; Mehlenbeck, Robyn; Jones, Margaret
Abstract: Objectives: To compare cardiometabolic biomarkers between age and sex-matched pairs of overweight/obese and healthy weight elementary-school aged Latino children. Methods: This was a case-control study in which cases, who were participating in a culturally-adapted pediatric weight management program targeting overweight/obese (BMI-for-age ≥85th percentile) Latino children, were age- and sex-matched to healthy weight (BMI-for-age between 5–85 th percentile) Latino children from the same community. Following an overnight fast, a venous blood sample was collected from participants and stored at −80°C for future batch analysis of the following: glycemic markers (insulin; hemoglobin A1C; glucose) for the calculation of HOMA-IR, lipids (total cholesterol; triglycerides; low-density and high-density lipoprotein [HDL]), hepatic markers (aspartate aminotransferase [AST]; alanine aminotransferase [ALT]), and the inflammatory marker C-reactive protein. Due to the limited sample size, a Mann Whitney U test was used to identify differences between groups and an alpha of 0.05 was used as the cutoff for significance. Results: A total of 13 pairs of case and control children participated in this study (46% male), median age 6.5 years (range, 5.3–9.6), and BMI-for age Z-score was 2.4 for cases and −0.2 for controls. When compared to controls, the median values were significantly higher for insulin ( P  = 0.003), hemoglobin A1C ( P  = 0.002), HOMA-IR ( P  = 0.003), triglycerides ( P  = 0.023) and C-reactive protein ( P  < 0.001) but, lower for HDL ( P  = 0.002). Hepatic markers were similar between groups. Conclusions: Latino children are at heightened risk for obesity and associated co-morbidities although, there are limited studies describing metabolic and hepatic biomarkers among young Latino children. Compared to age- and sex-matched healthy weight children, differences among cardiometabolic biomarkers were noted. Hence, suggesting some analytes may be more sensitive to excess weight and thus more useful to track in response to treatment among this population. Funding Sources: George Mason University, Potomac Health Foundation.